EFFECTS OF FEMALE LEADERSHIP ON TEACHERS’ PERCEIVED TRUST IN ART EDUCATION MANAGEMENT IN COLLEGES AND UNIVERSITIES, SHANXI PROVINCE - เยว่เซียว, หลิว; เสนาฤทธิ์, ประพัฒน์พงศ์; มูลเมือง, สุขุม (วารสารวิจัยธรรมศึกษา, 2023)
The objectives of this research were (1) To develop the measurement model of the effects female leadership on teachers’ perceived trust in art education management in colleges and universities, by taking into account teachers’ characteristics and organizational climate; (2) To study the factors affecting teachers' perceived trust in female leadership; (3) To decompose the effects of female leadership on teachers’ perceived trust; and (4) To compare the models of teachers’ perceived trust between teachers of different genders. A quantitative survey research was used in this study. The data were collected by using a Likert-type self-rating questionnaire, developed by the researcher, with an IOC score of 0.85 and a reliability coefficient score of 0.91, from 230 art teachers working in colleges and universities in Shanxi province. The statistics used for data analyses included descriptive statistics, confirmatory factor analysis, structural equation modelling, and likelihood ratio test respectively. The main findings were: (1) The measurement model of the effects of female leadership on teachers’ perceived trust consisted of all four hypothetical variables, i.e., female leadership, organizational climate, teachers’ characteristics, and teachers’ perceived trust (Chi-square =97.721; df=46; ratio= 2.124; p-value=.000; CFI=0.979; RMSEA=0.070); (2) Teachers’ perceived trust in art education management was affected by female leadership and organizational climate; (3) Female leadership exerted its influences on teachers’ perceived trust both directly and indirectly through organizational climate: and (4) There was no difference of perceived trust in female leadership between teachers of different genders.